Power Play at the United Nations: The Effects of Added Stakeholders in the Committee on World Food Security - Alana Stein (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
How have the recent reforms of the United Nations’ Committee on World Food Security changed the committee’s division of power? The reforms have created an important and significant shift in the dissemination of power within the Committee on World Food Security by allowing previously underrepresented stakeholders to have a much more prominent and influential role in the committee. This paper analyzes the shift in power through the perspectives of Karl Marx, Max Weber, and John Gaventa and evaluates grievances against the reforms by various sectors. The reforms have created a new space for class conflict to occur by adding groups with opposing interests to the committee. The reforms have also given a voice to groups who were previously unheard within the committee by granting them new means of participation while maintaining the bureaucratic structure of the organization. The reforms of the Committee on World Food Security were able to radically change the power dynamics of the committee, giving it a more comprehensive viewpoint on food security and providing the committee with greater clout due to its inclusion of a variety of diverse stakeholders.